DENTAL AGE ASSESSMENT USING DEMIRJIAN’S METHOD – A RADIOGRAPHIC STUDY - Anamaria Jurca; Luminita Lazar; Mariana Pacurar; Cristina Bica; Manuela Chibelean; Eugen Bud (European Scientific Journal, ESJ, 2014)
Dental age estimation on panoramic X-rays is very useful for pediatric dentists and orthodontists in choosing a treatment plan, without the need for any additional radiographic investigation. The aim of this study was to compare chronological and dental age using Demirjian’s method on children from Central Romania. The study was conducted on X-rays of 285 children aged between 6-13 years. Dental age was determined based on the degree of mineralisation of the seven left mandibular teeth, and t-tests were used to assess the difference between dental age and chronological age within each age category. Dental age was more advanced in girls in almost all age groups, whereas in boys just the 6-7 and 8-9 age groups presented a more advanced dental age. The results of our study show that Demirjian’s method has some limitations for a Romanian population, and that these standards are applicable only in certain age groups. Further research is required on a larger sample.